A Population-based Study of Traumatic Brain Injury Incidence and Mechanisms in New Zealand: 2021–2022 Compared With 2010–2011 - Jones, K; Theadom, A; Starkey, N; Zeng, I; Ameratunga, S; Barker-Collo, S; Wilkinson-Meyers, L; Ao, BT; Henry, N; McClean, LA; Chua, J; Haumaha, L; et al. (Elsevier, 2026)
Background: Monitoring traumatic brain injury (TBI) incidence and epidemiological patterns is important for evidence-based strategic planning, policy, prevention, and resource allocation. We revisited population-based estimates and examined patterns of TBI incidence (all ages, severities) in 2021–2022 compared with 2010–2011 in New Zealand (NZ). Methods: Examining an urban (Hamilton) and rural (Waikato District) region in NZ (May 2021–April 2022, unintentionally following the start of the COVID-19 pandemic), we calculated crude annual age-, sex-, ethnic-, urban/rural area- and mechanism-specific TBI incidence per 100,000 person-years with 95% Confidence Intervals (CI). Poisson regression was used to derive adjusted Risk Ratios (aRRs) to compare age-standardised rates between sex, ethnicity, and area groups. Direct standardisation was used to age-standardise rates to the world population. We calculated Incidence Rate Ratios (IRRs) with 95% CI to compare 2021–2022 with 2010–2011 age-standardised rates. Findings: Total TBI incidence per 100,000 person-years was 852 cases (95% CI 816–890), including 791 cases (756–828) of mild TBI, and 61 cases (52–72) of moderate to severe TBI. TBI affected males more than females (IRR 1.31, 95% CI 1.29–1.33), and urban more than rural residents (IRR 1.57, 1.43–1.73). Most TBI (61%) occurred in people aged 15–64 years and were due to falls (48%). European and Asian peoples had lower risk of TBI than Māori (aRRs 0.68, 0.31 respectively). Compared to 2010–2011, total TBI incidence and rates among Māori were stable; TBI incidence was greater among females, urban residents, and adults aged ≥34 years; and TBI due to falls significantly increased (IRR 1.20, 95% CI 1.03–1.40). Interpretation: Noting increased risks for underestimation due to COVID-19, findings suggest overall TBI incidence rate in NZ was similar in 2021–2022 to 2010–2011, while highlighting changes in TBI distribution. Age-, sex-, area-, ethnic-, and mechanism-specific distributions should be considered when revisiting prevention strategies to reduce TBI incidence. Funding: Health Research Council of New Zealand of NZ.
Keywords: Epidemiology; Incidence; Mechanism; Population-based; Traumatic brain injury; BIONIC and BIONIC2 Study Groups; 32 Biomedical and Clinical Sciences; 4206 Public Health; 42 Health Sciences; 3202 Clinical Sciences; Rural Health; Women's Health; Neurosciences; Brain Disorders; Health Disparities and Racial or Ethnic Minority Health Research; Health Disparities; Traumatic Brain Injury (TBI); Prevention; Physical Injury - Accidents and Adverse Effects; Minority Health; Traumatic Head and Spine Injury; 2.4 Surveillance and distribution; Injuries and accidents; 3202 Clinical sciences; 4203 Health services and systems; 4206 Public health